Response of parliamentary parties in the Republic of Slovenia to the mass arrivals of migrants - Klemenčič, Matjaž (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2017)
The mass arrivals of political and economic migrants in Slovenia started when Hungary closed its border with Croatia. In this article, we analyze the reactions of parliamentary parties in Slovenia, focusing on the media statements of their leaders and members on the significant events since the beginning of mass arrivals of migrants to date: first arrivals of migrants to Slovenia, erection of fences on Slovenian-Croatian border, November 2015 Paris terrorist attacks, protests against accommodation of minor migrants unaccompanied by adults in Student dorm in Kranj, proposal for consultative referendum on the acceptance of migrants in Slovenia and Act on amendments to the Aliens Act. We point out some of the most defining statements to show the political opinions of individual parties and compare the responses of these parties in the light of the political division between left-wing and right-wing politics as well as political division based on the urban-rural cleavage.
Keywords: migracije; human migration; imigranti; political party; politične stranke; mediji; communication medium; Slovenia; Slovenija